Efeitos do alho (allium sativum) in natura sobre salmonella infantis experimentalmente inoculada em frango de corte - Mota, Bárbara de Paiva (2015)
This study aimed to evaluate the effects of different doses of in natura garlic on the control of Salmonella Infantis and their consequence on performance, fecal excretion of Salmonella and blood parameters in experimentally inoculated broiler chickens. In this experiment we used 256 one-day-old male chicks, distributed in a completely randomized design with eight treatments, four replications with four replicates of eight birds each. The birds were orally inoculated at one-day-old with 0.5 ml of buffered saline, containing approximately 5.0 x 103 CFU / ml of Salmonella Infantis. Treatment 1 (T1) was the control group (Placebo); T2 - received garlic at a dose of 1.5%; T3 - received garlic at a dose of 3.0%; T4 - received garlic at a dose of 4.5%; T5 – was orally inoculated (Positive Control SI); T6 – was orally inoculated and treated with 1.5%; T7 – was orally inoculated and treated with 3.0%; T8 – was orally inoculated and treated with 4.5%. The performance was measured at seven, 21 and 35 days. At the days eight, 15 and 29 four birds for treatment were submitted to six hour fasting, and then they were weighed, euthanized, necropsied, and the organs were collected for weight determination and detection of Salmonella. Cloacal swabs were collected at three, 13, and 28 days and blood samples were collected at 14 and 36 days of age, after fasting for eight hours to evaluate blood parameters. At seven and 21 days, weight gain and final weight were lower in birds fed 4.5% of garlic, and there was no significant difference in the period of 1-35 days. The weight of the intestine and liver at 29 days was higher in birds inoculated and treated with 3.0% of garlic. Spleen weight was higher in birds inoculated at 29 days. Garlic did not inhibit Salmonella invasion in the spleen at the doses used. We found garlic did not reduce the intestinal E. coli population, but it reduced Salmonella. We observed garlic influenced cholesterol levels. In conclusion, fresh garlic in natura at the doses used does not alter the performance, as well as it does not inhibit the migration of Salmonella to the spleen; however, it influences serum cholesterol levels and reduces Salmonella fecal excretion of.